2011
DOI: 10.1007/s00403-011-1177-1
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial and axon reflex vasodilatation to acetylcholine in rosacea-affected skin

Abstract: Rosacea is a chronic skin disorder, characterized by persistent painful facial flushing and often accompanied by papules and pustules. To investigate the mechanism of facial flushing in rosacea, acetylcholine was administered by iontophoresis to a 10-mm diameter site in the forehead of 31 patients with rosacea and in 29 controls of similar age and sex distribution. During the iontophoresis, current strengths doubled in eight steps from 2.5 to 320 μA. For each step, skin blood flow was monitored during 60 s of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 26 publications
0
20
0
2
Order By: Relevance
“…67,82 For laser Doppler, absolute values are meaningless without measuring sympathetic flux changes and blood vessel density, which is impossible with noninvasive techniques. 89,118 Control for these factors was often not described or accounted for in the reviewed articles, and comparisons with normal skin were scarce. Additionally, biophysical tools are probe-related; they only cover a small facial area, questioning representativeness of the entire face.…”
Section: Discussionmentioning
confidence: 99%
“…67,82 For laser Doppler, absolute values are meaningless without measuring sympathetic flux changes and blood vessel density, which is impossible with noninvasive techniques. 89,118 Control for these factors was often not described or accounted for in the reviewed articles, and comparisons with normal skin were scarce. Additionally, biophysical tools are probe-related; they only cover a small facial area, questioning representativeness of the entire face.…”
Section: Discussionmentioning
confidence: 99%
“…Skin hypersensitivity and flushing augmentation have been directly linked to neural stimulation in rosacea . Sensory neuron density is moderately increased in the erythematotelangiectatic (ETR) subtype of rosacea, and increased density of TRP ion channels on sensory neurons, blood vessels and immune cells has also been reported across all cutaneous rosacea subtypes …”
Section: Rosacea Pathophysiologymentioning
confidence: 99%
“…Skin hypersensitivity and flushing augmentation have been directly linked to neural stimulation in rosacea. 36 open question with significant therapeutic implications ( Fig. 3).…”
Section: Neurogenic Inflammationmentioning
confidence: 99%
“…The psychosocial strain of rosacea is comparable to other conditions such as work‐related contact dermatitis or vitiligo . Rosacea patients have a higher incidence of shame , depressions , and social phobias , as a result of which they increasingly avoid social contact. Reduced quality of life was found in several studies and confirmed in a meta‐analysis .…”
Section: Psychosocial Aspects Of Rosaceamentioning
confidence: 99%